Method for preparing ferrovanadium-based alloy by reducing vanadium slag through silicothermic method and ferrovanadium-based alloy

The vanadium slag is reduced by silicon thermal method to prepare ferrovana vanadium-based alloys, which solves the problem of low recovery of valuable metal elements in the prior art, and realizes efficient recovery and preparation of low oxygen content alloys, significantly shortening the smelting process.

CN119736472APending Publication Date: 2025-04-01PANZHIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411902376.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the existing vanadium slag recycling methods, the recovery rate of valuable metal elements such as Cr, Ti, Fe, Mn is low and cannot be effectively utilized.

Method used

The vanadium slag was reduced by silicon thermal method, and the vanadium slag, industrial silicon and slag-making agent were dried, crushed, mixed and grinded, and then heated up and reduced and calcined in an argon atmosphere to prepare a ferrovana-based alloy.

Benefits of technology

It has achieved efficient recovery of valuable metal elements such as V, Cr, Ti, Fe and Mn from vanadium slag, and prepared a low-oxygen content of ferrous vanadium-based alloy, which significantly shortened the smelting process and improved production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736472A_ABST
    Figure CN119736472A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a ferrovanadium-based alloy by reducing vanadium slag through a silicothermic method and the ferrovanadium-based alloy, and belongs to the field of metallurgy. The method specifically comprises the steps that vanadium slag, industrial silicon and a slag former are dried, crushed, mixed and ground to obtain a mixed material, then the mixed material is placed in an argon atmosphere to be heated and subjected to reduction roasting, and the ferrovanadium-based alloy is obtained. The microstructure of the ferrovanadium-based alloy takes Ti, Fe, Si and Mn as main iron-based alloy phases, and the vanadium-based alloy taking Si, V and Cr as main components is segregated and enriched among crystals of the main iron-based alloy. According to the method, valuable metal elements such as V, Cr, Ti, Fe and Mn are recycled from the vanadium slag, the vanadium-iron-based alloy is prepared through separation, development and utilization of high-added-value products are carried out on the vanadium slag, and the problems that in an existing vanadium slag recycling method, the valuable metal elements such as Cr, Ti, Fe and Mn are low in recycling rate and cannot be effectively utilized can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgy, and in particular relates to a method for preparing a vanadium-iron-based alloy by reducing vanadium slag through a silicon thermal method and a vanadium-iron-based alloy. Background Art

[0002] After vanadium-titanium magnetite is processed by blast furnace-converter for vanadium extraction, vanadium slag and semi-steel are produced. Vanadium slag contains relatively high levels of valuable metal elements such as V, Cr, Ti, Fe, and Mn, and its mineral composition is spinel ((Fe, Mn)(V, Cr, Ti)2O4), olivine ((Fe, Mn)2SiO4) and pyroxene (Ca(Fe, Mg)Si2O6). Regarding the efficient resource utilization of vanadium slag, the current focus is on vanadium slag vanadium recovery of V resources, and there is little research on the coordinated recovery of V and Cr. Other valuable metal resources in vanadium slag cannot be effectively utilized.

[0003] The existing vanadium extraction process only extracts vanadium resources from vanadium slag, and the recovery rate of other valuable metals is low. The chromium ion content in vanadium extraction wastewater is high and needs special treatment before discharge. The alkali metal content in vanadium extraction waste slag is high, which is not conducive to the comprehensive utilization of resources. As the world pays more and more attention to resource and environmental issues, the reuse and recycling of industrial solid waste or by-products are increasingly concerned, and it is urgent to develop a green and efficient method for recovering valuable metal elements in vanadium slag.

[0004] The existing production process of vanadium-containing steel mainly involves tempering ferrovanadium by adding vanadium-containing semi-steel after vanadium extraction to obtain steel of different grades. Ferrovanadium uses vanadium slag as raw material to produce V2O5, and then reduces V2O5 to obtain ferrovanadium of different grades. The production process of this process is long, the vanadium yield of the whole process is low and the cost is high. In order to shorten the smelting process, domestic and foreign scholars have proposed two methods of direct alloying of vanadium slag and V2O5. When vanadium slag is directly alloyed, the amount of reducing agent ferrosilicon and vanadium slag is difficult to control, and SiO2 in vanadium slag and reduction products causes a significant increase in slag volume, aggravating lining erosion; direct alloying of V2O5 is to add V2O5 and reducing agent in the converter, which affects the steelmaking environment, such as the temperature of molten steel drops, the slag volume increases, and the composition of molten steel changes after adding materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is that in the existing method for recycling vanadium slag, the recovery rate of valuable metal elements such as Cr, Ti, Fe, Mn, etc. is low and they cannot be effectively utilized.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] In a first aspect, the present invention provides a method for preparing vanadium-iron-based alloy by reducing vanadium slag by silicon thermal method, specifically: vanadium slag, industrial silicon and slag-forming agent are dried, crushed, mixed and ground to obtain a mixed material, and then the mixed material is placed in an argon atmosphere to heat, reduce and roast to obtain the vanadium-iron-based alloy.

[0008] The components of the mixed material are 35-51% of vanadium slag, 29-35% of industrial silicon and 15-36% of slag-forming agent in terms of mass percentage.

[0009] The temperature of the above reduction roasting is 1823-1873K, and the time is 240-300min.

[0010] Furthermore, in the above method, the chemical composition of the vanadium slag is as follows by mass percentage: TFe 20-40%, MnO 15-23%, V2O3 10-15%, TiO2 8-12%, Cr2O3 6-10%, SiO2 10-14%, CaO 1-3.5%, Al2O3 1-5%, and MgO 1-3%.

[0011] Furthermore, in the above method, the composition of the slag-forming agent is CaO 61-78% by mass, and the rest is Al2O3.

[0012] Furthermore, in the above method, the purity of industrial silicon is ≥98%, the purity of CaO is ≥98%, and the purity of Al2O3 is ≥98%.

[0013] Furthermore, in the above method, drying is vacuum drying at 100-150° C. for 2-3 hours.

[0014] Furthermore, in the above method, the crushing is to crush the material to a particle size of less than -74 μm, accounting for more than 80%.

[0015] Furthermore, in the above method, the heating rate is 4 to 10°C / min.

[0016] In a second aspect, the present invention provides a vanadium-iron-based alloy prepared by the above method.

[0017] The microstructure of the above-mentioned vanadium-iron-based alloy is mainly composed of Ti, Fe, Si and Mn as iron-based alloy phases, and the vanadium-based alloy mainly composed of Si, V and Cr is segregated and enriched between the crystals of the main iron-based alloy.

[0018] The chemical composition of the above-mentioned vanadium-iron-based alloy is as follows by mass percentage: Si 30-32%, Fe 27-28%, Mn 19-20%, V9-10%, Cr 6-7%, and Ti 5-6%.

[0019] The beneficial effects of the present invention are as follows: in view of the problems existing in the prior art, the present invention innovatively proposes a new path for smelting vanadium-iron-based alloys in one step using vanadium slag, that is, a method for preparing vanadium-iron-based alloys by reducing vanadium slag by silicon thermal method. The method of the present invention uses vanadium slag as raw material, based on silicon thermal method reduction, combined with the process parameters such as smelting temperature, holding time and slag composition specially set by the present invention, to achieve the recovery of valuable metal elements such as V, Cr, Ti, Fe and Mn from vanadium slag, separate and prepare vanadium-iron-based alloys, and develop and utilize vanadium slag for high value-added products.

[0020] During the silicon thermal reduction of vanadium slag, the composition of the slag is mainly CaO-SiO2-Al2O3 slag system. As the reduction reaction continues, the SiO2 content in the slag continues to increase. The increase in SiO2 content will inhibit M x O y According to the process of the present invention, the addition amount of vanadium slag, reducing agent and slag-forming agent is controlled, and the reduction roasting temperature and time of the present invention are combined to promote the silicon thermal reduction reaction, which is beneficial to strengthen the M x O y The invention can ensure product quality and effectively avoid the problem of significant increase in slag volume and aggravated lining erosion caused by SiO2 in the prior art.

[0021] The present invention is based on a one-step method for preparing vanadium-containing iron-based alloys using vanadium slag. Compared with the existing process of smelting alloys using vanadium slag, the process method of the present invention significantly shortens the process flow of the prior art. At the same time, the present invention is based on reasonable slag making by silicon thermal reduction of vanadium slag, realizes efficient separation of slag and gold, and prepares vanadium-containing iron-based alloys with low oxygen content. Compared with the existing process of direct alloying of vanadium slag, the present invention significantly reduces the difficulty of production process control and solves the problem of difficult control of the amount of reducing agent ferrosilicon and vanadium slag added in the prior art.

[0022] The preparation method of the present invention has a short process flow and high production efficiency. The obtained vanadium-containing iron-based alloy has a low oxygen content and can be directly used for preparing alloy additives for special steel. Based on the process method of the present invention and the vanadium slag used, combined with the process parameters set by the present invention, the main phases of the obtained vanadium-containing iron-based alloy are: VSi2, V3Si, Fe, FeSi2, TiFeSi2, Mn, MnSi, TiMnSi2, Cr3Si, etc. Under the optimal process conditions, the recovery rates of Fe, Cr, Mn, V and Ti in the vanadium slag are: 92.57%, 92.25%, 90.41%, 89.71% and 79.36% respectively. The technical scheme of the present invention realizes the reduction and recovery of valuable metal elements in vanadium slag to different degrees, and has a high value of popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1The macroscopic structure of the longitudinal section of the sample after solidification at different reduction roasting temperatures;

[0024] Figure 2 The macroscopic structure of the longitudinal section of the solidified sample at different reduction roasting times;

[0025] Figure 3 It is the recovery rate of valuable metal elements in vanadium slag under the optimal process conditions (Example 1). DETAILED DESCRIPTION

[0026] The technical solution of the present invention can be specifically implemented in the following manner.

[0027] 1. Silicon thermal reduction of vanadium slag to prepare vanadium-iron-based alloy, specifically comprising the following steps:

[0028] 1. Put the vanadium slag, industrial silicon and slag-forming agent into a vacuum drying oven, set the vacuum degree to 0.05MPa, the temperature to 120℃, and dry for 2h. Put the dried raw materials into a sealed sample making machine for crushing for 15min, so that the proportion of particles below -74μm is more than 80%. Then, weigh the dried and crushed vanadium slag, industrial silicon and slag-forming agent according to the ratio shown in Table 1, put them into an agate mortar and grind them for 20min, and put the ground mixed raw materials into a corundum crucible.

[0029] Table 1 Raw material ratio

[0030]

[0031] In Table 1, the chemical composition of the vanadium slag, by mass percentage, is: TFe 24.90%, MnO 20.66%, V2O3 12.67%, TiO2 9.06%, Cr2O3 8.66%, SiO2 13.77%, CaO 3.11%, Al2O3 1.25%, MgO 1.92%; the industrial silicon is metallurgical grade industrial Si (purity 98%), Al2O3 (analytical grade, 98%) and CaO (analytical grade, 98%).

[0032] 2. Place the corundum crucible containing the material into a vacuum box resistance furnace, first evacuate the furnace to a vacuum degree of 0.01MPa, introduce argon gas to normal pressure, repeat three times to maintain the argon atmosphere in the furnace; then turn on the heating system, raise the temperature to the set temperature at 5℃ / min, keep the temperature for a predetermined time, and then cool the crucible to room temperature under argon protection with the furnace to obtain vanadium-iron-based alloy. The specific process is shown in Table 2.

[0033] Table 2 Reduction roasting process

[0034]

[0035]

[0036] 2. Detection and analysis of vanadium-iron-based alloy, the specific results are as follows:

[0037] 1. Figure 1 The figures are the macroscopic structures of the longitudinal sections of the samples after solidification at different reduction roasting temperatures; among them, (a) is comparative example 1, (b) is comparative example 2, (c) is example 1, and (d) is example 2.

[0038] Depend on Figure 1 It can be seen that under different reduction temperature conditions, the slag and the alloy have a clear and obvious separation boundary, and the alloy is enriched at the bottom of the crucible, as indicated by the yellow dotted line in the figure. However, when the reduction temperature is 1723K and 1773K, there are dispersed fine alloy particles on the upper layer of the slag, such as Figure 1 (a) and Figure 1 The red dotted line in (b) indicates that at the reduction temperatures of 1823K and 1873K, the dispersed fine alloy particles have aggregated and sunk, as shown in Figure 2. Figure 1 (c) and Figure 2 (d) is indicated by the green solid line. This shows that when the reduction temperature is low, the viscosity of the slag inhibits the agglomeration of the fine alloy particles, and the reduced fine alloy particles are difficult to agglomerate, resulting in the inability of the fine alloy particles with smaller mass to deposit. Due to the low temperature, even the larger alloy particles that are agglomerated and deposited do not fuse with the main alloy at the bottom, but are in the interface area between the main alloy and the slag. As the reduction temperature increases, the inhibitory effect of the slag viscosity weakens, and the agglomerated alloy particles in the interface area between the main alloy and the slag fuse. When the reduction temperature is greater than 1823K, the interface between the slag and the alloy is clearer, and the deposited alloy particles in the interface area are integrated into the main alloy. It can be seen that by adopting the reduction roasting temperature specified in the present invention, the reduced alloy particles can agglomerate, deposit and fuse, and the slag and alloy separation effect is good.

[0039] 2. Figure 2 The figures are the macroscopic structures of the longitudinal sections of the solidified samples at different reduction roasting times; among them, (a) is Comparative Example 3, (b) is Comparative Example 4, (c) is Example 1, and (d) is Example 3.

[0040] Depend on Figure 2 It can be seen that under different reduction time conditions, the solidified samples all showed obvious slag-gold separation, with a clear separation boundary between the alloy and the slag, and the alloy was enriched at the bottom of the crucible, as indicated by the yellow dotted line in the figure. When the reduction time was 120 min, there were dispersed fine alloy particles on the upper layer of the slag, such as Figure 2 The red dotted line in (a) indicates that the reduction reaction time is insufficient and the reduced fine alloy particles have not yet agglomerated and sunk. As the reduction time increases, the dispersed fine alloy particles gradually agglomerate and settle. Figure 2The green solid line marks the area in (c)-(d). When the reduction time is 120 min, there is a slag-metal mixed area at the junction of the slag and the alloy. As the reduction time increases, the slag-metal mixed area gradually decreases, such as Figure 2 The solid green line marks the area. In addition, Figure 2 (a) and Figure 2 The alloy volume in (b) is relatively large, indicating that when the reduction time is less than 240 min, there is slag inclusion in the alloy structure, and the original slag at the bottom has not had time to float up and separate. It can be seen that only by adopting the reduction roasting time limited by the present invention can the agglomeration and sinking of the reduced fine alloy particles be ensured, and the melting and floating of the original slag at the bottom be ensured.

[0041] 3. The macroscopic organizational structure of the longitudinal section of the solidified samples under different chemical compositions of slag-forming agents (Example 1, Examples 4-6) was observed, and it was found that the solidified samples obtained with different slag-forming agent compositions all showed obvious slag-gold separation, the separation boundary between the alloy and the slag was clear, and the alloy was enriched at the bottom of the crucible.

[0042] At the same time, the sample slags obtained under different chemical compositions of slag-forming agents (Example 1, Example 4-6) were subjected to M x O y Content analysis: It was found that the FeO and TiO2 contents in the slag composed of the slag-forming agent of Example 1 were the lowest, and the FeO and TiO2 contents in the slag-forming agents of Examples 4-6 decreased successively. The contents of V2O3, MnO and Cr2O3 in the slags composed of the four slag-forming agents were basically the same, and were little affected by the changes in the slag-forming agent composition.

[0043] During the silicon thermal reduction of vanadium slag, the composition of the slag is mainly CaO-SiO2-Al2O3 slag system. As the reduction reaction continues, the SiO2 content in the slag continues to increase, and the increase in SiO2 content will inhibit M x O y The CaO content in the slag can promote the silicon thermal reduction reaction, which is beneficial to strengthen the M x O y Therefore, by using the chemical composition of the slag-forming agent defined in the present invention, the vanadium slag can be reduced to a vanadium-iron-based alloy with an iron-based alloy phase as the main phase and a vanadium-based alloy phase as the segregation phase. x O y From the perspective of content, the slag-forming agent composition of Example 1 has the best effect on silicon thermal reduction of vanadium slag.

[0044] 4. In the technical solution of the present invention, under high temperature, the slag-making agent and vanadium slag are transformed into a molten state during the reduction process, and the spinel phase, olivine phase and pyroxene phase in the vanadium slag are decomposed to form M x O y The added silicon is partly used as a reducing agent to make Mx O y Reduced to the corresponding metal, Si is converted into SiO2 and dissolved in the slag. The remaining silicon reacts with the reduced metal elements as a capture agent to form four types of alloy phases. Type I phase is mainly Si, Fe and Mn, Type II is mainly Si, Ti, Fe and Mn, Type III is mainly Si, Fe and Mn, and Type IV is mainly Si, V and Cr. The fine particles of these four types of alloys continue to agglomerate, grow and sink, and finally settle to the bottom of the experimental crucible to form a vanadium-iron based alloy.

[0045] XRD and EPMA analysis were performed on the vanadium-iron-based alloys obtained in Examples 1-6, and the results showed that the main phases in the alloys obtained by the present invention included VSi2, V3Si, Fe, FeSi2, TiFeSi2, Mn, MnSi, TiMnSi2 and Cr3Si, etc. The microstructure morphology of the obtained vanadium-titanium-based alloy was detected by electron probe-Popsk analysis (EPMA-WDS), and the obtained vanadium-iron-based alloys can be roughly divided into three types of alloy systems: Fe-Mn-Si alloy, Fe-Ti-Si alloy and V-Cr-Si alloy. Combined with XRD phase analysis, it can be seen that Fe-Mn-Si alloys mainly include (Fe, Mn) Si, (Fe, Mn) Si2, (Fe, Mn) Si and (Fe, Mn) Si2, Fe-Ti-Si alloys mainly include Ti(Fe, Mn) Si2, and V-Cr-Si alloys mainly include VSi2, V3Si and Cr3Si, etc. Vanadium-iron-based alloy is mainly based on Fe-Mn-Si, with V-Cr-Si alloy enriched in intergranular segregation, and Fe-Ti-Si alloy is easily dissolved with Fe-Mn-Si alloy; that is, the microstructure of vanadium-iron-based alloy is mainly iron-based alloy phase with Ti, Fe, Si and Mn, and vanadium-based alloy with Si, V and Cr as the main phases is segregated and enriched between the crystals of the main iron-based alloy.

[0046] Under the optimal process conditions (Example 1), the present invention detects, analyzes and calculates the recovery rate of valuable metal elements in vanadium slag and the main components of vanadium-iron-based alloy. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the recovery rate of valuable metal elements in vanadium slag is in descending order: Fe, Cr, Mn, V and Ti, and the corresponding recovery rates are: 92.57%, 92.25%, 90.41%, 89.71% and 79.36%. Through analysis and calculation, it can be known that the main components of the obtained vanadium-iron-based alloy are: Si is 31.45wt.%, Fe is 27.38wt.%, Mn is 19.27wt.%, V is 9.03wt.%, Cr is 6.89wt.%, and Ti is 5.98wt.%, so that the valuable metal elements in vanadium slag are recovered to different degrees.

Claims

1. A method for preparing vanadium-iron-based alloy by reducing vanadium slag by silicon thermal method, characterized in that: The vanadium slag, industrial silicon and slag-forming agent are dried, crushed, mixed and ground to obtain a mixed material, and then the mixed material is placed in an argon atmosphere for heating and reduction roasting to obtain a vanadium-iron based alloy; The composition of the mixed material is 35-51% of vanadium slag, 29-35% of industrial silicon, and 15-36% of slag-forming agent in terms of mass percentage; The reduction roasting temperature is 1823-1873K, and the time is 240-300min.

2. The method for preparing vanadium-iron-based alloy by silicon thermal reduction of vanadium slag according to claim 1, characterized in that: The chemical composition of the vanadium slag is as follows by mass percentage: TFe 20-40%, MnO 15-23%, V2O3 10-15%, TiO2 8-12%, Cr2O3 6-10%, SiO2 10-14%, CaO 1-3.5%, Al2O3 1-5%, and MgO 1-3%.

3. The method for preparing vanadium-iron-based alloy by silicon thermal reduction of vanadium slag according to claim 1, characterized in that: The composition of the slag-forming agent is CaO 61-78% by mass, and the rest is Al2O3.

4. The method for preparing vanadium-iron alloy by silicon thermal reduction of vanadium slag according to claim 3, characterized in that: The purity of the industrial silicon is ≥98%, the purity of CaO is ≥98%, and the purity of Al2O3 is ≥98%.

5. The method for preparing vanadium-iron-based alloy by silicon thermal reduction of vanadium slag according to claim 1, characterized in that: The drying is performed under vacuum at 100-150° C. for 2-3 hours.

6. The method for preparing vanadium-iron-based alloy by silicon thermal reduction of vanadium slag according to claim 1, characterized in that: The crushing is to crush the material to a particle size of less than -74 μm, accounting for more than 80%.

7. The method for preparing vanadium-iron-based alloy by silicon thermal reduction of vanadium slag according to claim 1, characterized in that: The heating rate is 4-10°C / min.

8. Vanadium-iron-based alloy, characterized in that: Prepared by the method according to any one of claims 1 to 7.

9. The vanadium-iron-based alloy according to claim 8, characterized in that: The microstructure of the vanadium-iron-based alloy is mainly composed of Ti, Fe, Si and Mn as the iron-based alloy phase, and the vanadium-based alloy mainly composed of Si, V and Cr is segregated and enriched between the crystals of the main iron-based alloy.

10. The vanadium-iron-based alloy according to claim 8, characterized in that: The chemical composition of the vanadium-iron-based alloy is as follows by mass percentage: Si 30-32%, Fe 27-28%, Mn 19-20%, V 9-10%, Cr 6-7%, and Ti 5-6%.